2013
DOI: 10.5194/acp-13-2321-2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the chemical composition of rainwater throughout Hurricane Irene

Abstract: Abstract. Sequential sampling of rainwater from Hurricane Irene was carried out in Wilmington, NC, USA on 26 and 27 August 2011. Eleven samples were analyzed for pH, major ions (Cl−, NO3−, SO42−, Na+, K+, Mg2+, Ca2+, NH4+), dissolved organic carbon (DOC) and hydrogen peroxide (H2O2). Hurricane Irene contributed 16% of the total rainwater and 18% of the total chloride wet deposition received in Wilmington NC during all of 2011. This work highlights the main physical factors influencing the chemical composition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…Low levels of Na deposition, likely of little direct consequences to plants, enhanced decomposition in this study; low-levels of Na delivery by hurricanes, to otherwise Na-impoverished ecosystems, have a similar potential to enhance ER. Aerosol deposition of Na and other marine ions peak during tropical storms (Miller et al 2008, Mullaugh et al 2012. Moreover, anecdotal accounts from New England suggest hurricanes can deposit Na far inland.…”
Section: Caveats and Future Workmentioning
confidence: 99%
“…Low levels of Na deposition, likely of little direct consequences to plants, enhanced decomposition in this study; low-levels of Na delivery by hurricanes, to otherwise Na-impoverished ecosystems, have a similar potential to enhance ER. Aerosol deposition of Na and other marine ions peak during tropical storms (Miller et al 2008, Mullaugh et al 2012. Moreover, anecdotal accounts from New England suggest hurricanes can deposit Na far inland.…”
Section: Caveats and Future Workmentioning
confidence: 99%
“…Dissolved OC concentrations during Hurricane Sandy ranged from 0.43 to 1.61 mg C L −1 over the course of the event, with an average concentration of 0.90 mg C L −1 (Table , Figure ). This average concentration is higher than the concentrations of 0.31 mg C L −1 reported from sequential samples collected during tropical storm Ernesto (Miller et al, ), and 0.19 mg C L −1 during Hurricane Irene in Wilmington (NC, USA; Mullaugh et al, ), but lower than concentration of 2.30 mg C L −1 reported from a composite sample from Hurricane Irene in Greenville (NC, USA; Mitra et al, ) . Those studies during extreme events were from coastal locations (Wilmington and Greenville, NC), whereas our observations are the first to consider changes in quantity and quality of precipitation DOC during a hurricane as it followed an inland track.…”
Section: Resultsmentioning
confidence: 60%
“…Several addressed variability of DOC and its components in precipitation during typical‐frequency events in South America (Germer et al, ; Zimmermann, Wilcke, & Elsenbeer, ), Japan (Sempéré & Kawamura, ; Taguchi et al, ), and the United States (Kawamura, Steinberg, & Kaplan, ). Others focused on dynamics during extreme events such as tropical storms and hurricanes in the United States (Miller, Willey, & Kieber, ; Mullaugh, Willey, Kieber, & Mead, ; Willey et al, ). In general, studies found that concentrations of DOC can be variable during events (Germer et al, ; Kawamura et al, ) or change very little (Zimmermann et al, ) and are influenced by storm characteristics (Mullaugh et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations